Miasto atraktycjne – miastem konkurencyjnym - Jancz, Joanna (Refleksje. Pismo naukowe studentów i doktorantów WNPiD UAM, 2017)
The purpose of this paper is to show that modern cities must be attractive to be competitive for investors, tourists and residents. The pivotal question is how they build their attraction and what factors are important for investors. The article characterizes the term cities and problems which will be a barrier to the development in the cities.